Episodic Mydriasis as Migraine Equivalent - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
A 14-year-old girl who presented with yearly attacks of bilateral internal ophthalmoplegia, nausea and headache since the age of 9 is the subject of a case report from the Department of Child Neurology, University Hospital Nijmegen, The Netherlands.